2020
DOI: 10.1016/j.mce.2020.110918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural pesticides on the reproductive system of aquatic wildlife species, with crocodilians as sentinel species

Abstract: Effects of agricultural pesticides on the reproductive system of aquatic wildlife species, with crocodilians as sentinel species,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 123 publications
1
8
0
Order By: Relevance
“…For example, propazine has scarcely been examined in this respect, and the effects of atrazine on sperm have been studied to a limited extent only. As found in other studies, atrazine can behave as an anti-androgen, xenoestrogen and oestrogen agonist [37]. Epidemiological studies conducted in USA have revealed sperm concentration and motility to be reduced by atrazine exposure in humans [38].…”
Section: Introductionsupporting
confidence: 62%
“…For example, propazine has scarcely been examined in this respect, and the effects of atrazine on sperm have been studied to a limited extent only. As found in other studies, atrazine can behave as an anti-androgen, xenoestrogen and oestrogen agonist [37]. Epidemiological studies conducted in USA have revealed sperm concentration and motility to be reduced by atrazine exposure in humans [38].…”
Section: Introductionsupporting
confidence: 62%
“…American alligators ( Alligator mississippiensis ; Order Crocodilia) are an effective model to study environmental health and the effects of EDCs (Finger & Gogal, 2013; Tavalieri et al, 2020). Alligator mississippiensis is a long‐lived, top‐trophic predator, meaning that EDC concentrations and physiological effects may be biomagnified (or have increased deposition) in relatively old individuals (Heinz et al, 1991; Roe et al, 2004; Finger & Gogal, 2013; Tavalieri et al, 2020). In addition, like other reptiles, environmental conditions mediate development (Joanen & Mcnease, 1989), growth (Lance, 2003), and homeostasis (Seebacher et al, 2003) in A. mississippiensis .…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown through docking studies and bioinformatic analysis that ES can bind to the ligand-binding site of the androgen receptor with considerable energy compared to its natural ligand dihydrotestosterone in the previous study ( Sebastian and Raghavan, 2015a ). The reproductive toxicity of ES is not limited to mammals but also extended to various other animals like zebrafish ( Han et al, 2011 ), crocodiles ( Tavalieri et al, 2020 ), C. elegans ( Du et al, 2015 ) and Newt ( Park et al, 2001 ) indicating that it could affect most forms of life in the ecosystem.…”
Section: Discussionmentioning
confidence: 99%